Management management and organizational climate in five educational institutions. Villa María del Triunfo. Lima - Mozombite Valdivieso, Horocia (2024)
The scientific study that we have carried out is of a basic nature, non-experimental causal correlational. The study elements are two: the administration of the Director and the organizational environment of the teachers at the primary level of the educational institutions in the district of Villa Maria del Triunfo, Lima in 2013. The population includes 356 teachers and administrators, and the final sample was made up of 185 teachers from the educational centers of Villa María del Triunfo. The structure of the study is transectional, correlational and causal. cross-sectional, bivariate. Two structured surveys were developed as a measurement for data collection, which include two aspects: to evaluate the organizational environment with its dimensions: Communication, trust, motivation for participation and leadership, which includes 38 questions. On the other hand, the second is the point of view of the teacher and the administrator, which includes 14 questions about the Director's administration that were asked of the 40 teachers in the sample. The tools satisfy the characteristics of validity according to expert juries and reliability. The research proposes the following research hypothesis: the Administrative Administration of the director has an impact on the Organizational Climate at the primary level of the educational institutions in the district of Villa María del Triunfo, Lima. According to Spearman's Rho correlation of 0.426, there is a moderately significant association between the variables. Furthermore, according to the highly relevant independence tests (***p <.000), the hypothesis is supported: